O nauczaniu literatury we Francji = About teaching literature in France - Magnuszewska, Zofia (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The model of a modern school nowadays, its function in society and also the development of civilization exert an influence on the aims and the selection of the content and methods of teaching literature at school France, a country with a particularly high standard of literary education, was the place where the changes introduced in the 60's and connected with the reorganization of the educational system on any level, stimulated a very animated discussion among scholars as well as teachers.
Keywords: dydaktyka literatury; Francja